2018
DOI: 10.1177/0961203318783052
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular reflex tests in patients with systemic lupus erythematosus: clinical performance and utility

Abstract: Background This review summarizes current knowledge about cardiovascular reflex tests (CVRTs) and other selected autonomic nervous system (ANS) assessment tests in systemic lupus erythematosus (SLE) patients and assesses their clinical utility in this group of patients. Methods The PubMed database was searched for terms associated with CVRTs and SLE. Only papers available in full text and published in English were considered. Ultimately, 13 were selected and analyzed. Results In most of the studies CVRTs resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…In previous studies, the prevalence of CART-based CAN has ranged from 23.5% to 82.7%, proposedly caused by methodological inconsistency, unstandardised test conditions and varying age of the studied populations. 2 Two authors, Stojanovich et al 9 and Milovanovic et al , 32 report on two SLE populations, resembling ours by age, and reported higher CAN prevalences (79.6% and 82.7%) than in the current study. Like in the current study, both authors considered CAN present when two or more of the CARTs were abnormal.…”
Section: Discussionsupporting
confidence: 76%
“…In previous studies, the prevalence of CART-based CAN has ranged from 23.5% to 82.7%, proposedly caused by methodological inconsistency, unstandardised test conditions and varying age of the studied populations. 2 Two authors, Stojanovich et al 9 and Milovanovic et al , 32 report on two SLE populations, resembling ours by age, and reported higher CAN prevalences (79.6% and 82.7%) than in the current study. Like in the current study, both authors considered CAN present when two or more of the CARTs were abnormal.…”
Section: Discussionsupporting
confidence: 76%
“…Systemic scleroderma and SLE are chronic autoimmune disorders of the connective tissue in which dysfunction of multiple organs, including the autonomic nervous system, is observed. 54,55 Importantly, systemic scleroderma and SLE are known to be much more prevalent in females than in males and the majority of SLE patients have affected kidneys. Lupus nephritis occurs in more than half of patients with SLE and approximately 10% of these patients develop ESRD and require hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Item scores are summed, and then divided for a final score out of 7. Scores of more than 4.7/7 are considered clinically relevant for fatigue associated with ANS dysfunction 18,19…”
Section: Methodsmentioning
confidence: 99%